How small cities are stimulating creativity and innovation - Bogilović, Sabina (Dynamic relationships management journal, 2020)
This paper examines creative city incentives of Ljubljana and small to medium-sized European cities (Bratislava, Tallinn, and Edinburgh) according to the type of creative city (technological-innovative, cultural-intellectual, cultural-techno-logical, and technological-organizational) they are. The paper utilizes a case study approach, because it allows in- depth research of the particular object, taking into account multiple dimensions. Based on secondary data of the Cultural and Creative Cities Monitor from the European Commission and European Smart Cities, we provide evidence that Ljubljana and Bratislava belong to the cultural-intellectual type, Tallinn is technological-innovative, and Edinburgh is a cultural-technological type of creative city.
Keywords: creative city; creativity; inovacije; Ljubljana; management; mesta; policymaking; razvojna politika; smart city; umetna inteligenca; ustvarjalnost